Acid sphingomyelinase regulates TH2 cytokine release and bronchial asthma. Issue 3 (8th October 2019) - Böll, Svenja; Ziemann, Sebastian; Ohl, Kim; Klemm, Patricia; Rieg, Annette D.; Gulbins, Erich; Becker, Katrin Anne; Kamler, Markus; Wagner, Norbert; Uhlig, Stefan; Martin, Christian; Tenbrock, Klaus; et al.
Abstract: Background: Allergic diseases and especially allergic asthma are widespread diseases with high prevalence in childhood, but also in adults. Acid sphingomyelinase (ASM) is a key regulator of the sphingolipid pathway. Previous studies defined the association of ASM with the pathogenesis of TH 1‐directed lung diseases like cystic fibrosis and acute lung injury. Here, we define the role of ASM in TH 2‐regulated allergic bronchial asthma. Methods: To determine the role of Asm under baseline conditions, wild‐type (WT) and Asm −/− mice were ventilated with a flexiVent setup and bronchial hyperresponsiveness was determined using acetylcholine. Flow cytometry and cytokine measurements in bronchoalveolar lavage fluid and lung tissue were followed by in vitro TH 2 differentiations with cells from WT and Asm −/− mice and blockade of Asm with amitriptyline. As proof of principle, we conducted an ovalbumin‐induced model of asthma in WT‐ and Asm −/− mice. Results: At baseline, Asm −/− mice showed better lung mechanics, but unaltered bronchial hyperresponsiveness. Higher numbers of Asm −/− T cells in bronchoalveolar lavage fluid released lower levels of IL‐4 and IL‐5, and these results were paralleled by decreased production of typical TH 2 cytokines in Asm −/− T lymphocytes in vitro. This phenotype could be imitated by incubation of T cells with amitriptyline. In the ovalbumin asthma model, Asm −/− animals were protected from high disease activity and showed better lung functions and lower levels of eosinophils and TH 2 cytokines. Conclusion: Asm deficiency could induce higher numbers of TH 2 cells in the lung, but those cells release decreased TH 2 cytokine levels. Hereby, Asm −/− animals are protected from bronchial asthma, which possibly offers novel therapeutic strategies, for example, with ASM blockade. Abstract : This study investigated the role of acid sphingomyelinase (Asm) in allergic bronchial asthma. Asm deficiency resulted in reduced TH 2 cytokine release both in vitro and in vivo. In the ovalbumin model, ASM −/− mice were protected from bronchial asthma, showed decreased production of TH 2 cytokines and lower number of eosinophils. Abbreviations: Asm, acid sphingomyelinase; BALF, bronchoalveolar lavage fluid; OVA, ovalbumin